2014
DOI: 10.1136/jclinpath-2013-202146
|View full text |Cite
|
Sign up to set email alerts
|

Lymph node revealing solutions in colorectal cancer: should they be used routinely?

Abstract: The Royal College of Pathologists (RCPath) and College of American Pathologists recommend that at least 12 lymph nodes should be harvested for adequate staging of colorectal carcinoma. Just one nodal tumour deposit upstages the malignancy from pN0 to pN1. This is critically important as node-positive patients (pN1) are considered for adjuvant chemotherapy whereas node-negative patients (pN0) may not be. It is not always easy to harvest the required number, especially in patients with rectal carcinoma who may h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 42 publications
1
16
1
Order By: Relevance
“…An increase in the total number of LNs per specimen has been reported with the use of a number of fat clearing techniques, including acetone [14,15,[18][19][20][21][22]. All these studies reported changes in the lymph node status (pN).…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the total number of LNs per specimen has been reported with the use of a number of fat clearing techniques, including acetone [14,15,[18][19][20][21][22]. All these studies reported changes in the lymph node status (pN).…”
Section: Discussionmentioning
confidence: 99%
“…High-resolution pelvic MRI is widely considered the optimal imaging method for rectal cancer [ 3 ], and it enables precise identification of high-risk factors, such as the extent of tumor invasion, extramural vascular invasion (EMVI) and the potential circumferential resection margin (CRM) [ 18 ]; however, the prediction of regional node metastases remains a challenge. Size is the usual criterion for metastatic nodes using MRI; however, the considerable size overlap between benign and malignant nodes affects the overall predictive value [ 19 ]. We found similar results in this study.…”
Section: Discussionmentioning
confidence: 99%
“…After the cut-out, the slices were packaged in gauze in numerical order from the aboral to the oral end. The packages were, subsequently, placed in a GEWF solution (Glacial acetic acid, Ethanol, distilled Water, and Formaldehyde) for at least 48 h to optimize the lymph node yield [ 23 ].…”
Section: Methodsmentioning
confidence: 99%